PREVENTIVE EFFORTS ON TERRORISM CRIMINAL MANAGEMENT IN INDONESIA - Bayu Wirayuda, Ketut (Ganesha Civic Education Journal, 2020)
Terrorism is a crime against humanity (Crime Against Humanity), and is a serious threat to the sovereignty of each country because terrorism is an international crime that poses a danger to security, world peace and detrimental to the welfare of the community needs to be done in a planned and sustainable eradication so that human rights many can be protected and held in high esteem. Terrorism has been rife in various countries including in Indonesia, many causes of terrorism in Indonesia are examples such as weak rules in Indonesia, Indonesia's defense system is also considered weak and there are those who support the occurrence of terrorism in Indonesia. In order for terrorism not to occur in Indonesia, rules must be made relating to terrorism that will cause people or perpetrators to commit acts of terrorism. Apart from its legal rules, efforts that can be done by the government are by improving the legal system or renewing the legislation system concerning terrorism and forming a body / apparatus specifically dealing with terrorism. With the establishment of a strict legal regulation, the apparatus or a strict legal entity to deal with terrorism, it is not difficult to commit terrorism in Indonesia. Many want to become terrorists in Indonesia because they are enticed by entering heaven, a luxurious life and a comfortable life in Indonesia, if the rules, legal apparatus and legal system are still weak then terrorism will be difficult to handle in Indonesia.